Iluzja upełnomocnienia jako środka emancypacji w edukacji i poprzez edukację - Czerepaniak-Walczak, Maria (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
Critical pedagogy still keeps asking, drills down questions about the possibility of using the emancipatory potential of empowering participants in interactions and educational processes to experience their freedom and responsibility. Both emancipation and empowerment are bandwagons of jargon words in (not only critical) education. The text focuses attention and argumentation on the simplified, sometimes naive, identification of these two concepts leading to misunderstandings and logical simplifications in reasoning, and even worse, in practice. Each of these terms refers to different phenomena, different social and educational practices, with different sources, processes, and consequences. The introduction of these terms into pedagogy without the prior definition of their meaning generates confuses. This refers not only to emancipation, which in common understanding is (incorrectly) identified with the liberation of women but also to empowerment, usually understand in pedagogy as a promise of management by participants of educational interactions of their own actions. In argumentation are using the specific features of these two phenomena with an indication of the differences between them. The central category differentiating the two experiences is the source of freedom, namely internal in the process of emancipation and external in empowerment. The illusion of liberation through empowerment in the educational process is indicated. The traps of developmental isonomy are presented as examples of it.
Keywords: utopia; education; emancipation; empowerment; traps of developmental isonomy